A Strategic Model for Institutionalizing Data Ethics and Legal Compliance in Health Networks - Damilola Oluyemi Merotiwon; Opeyemi Olamide Akintimehin; Opeoluwa Oluwanifemi Akomolafe (International Journal of Scientific Research in Civil Engineering, 2024)
As health networks increasingly rely on data-driven operations, the ethical and legal challenges surrounding patient data governance have intensified. This paper presents a strategic model designed to institutionalize data ethics and legal compliance within complex healthcare ecosystems. Drawing upon interdisciplinary frameworks from data governance, bioethics, legal informatics, and health information management, the model addresses the need for transparent data practices, equitable decision-making, and robust regulatory adherence. The proposed framework incorporates five critical pillars: ethical data stewardship, regulatory alignment, organizational accountability, technological safeguards, and continuous education. Through an extensive literature review and case study analysis of health systems in multiple jurisdictions, the model demonstrates practical pathways for embedding ethical and legal principles into data workflows, risk management protocols, and leadership strategies. The model was validated using a Delphi panel of 35 healthcare compliance professionals and informatics experts, followed by pilot implementations in two large hospital networks. Results indicated a significant improvement in regulatory audit readiness, reduction in ethical breaches, and enhanced stakeholder trust. This study offers actionable insights for health administrators, policymakers, and technology vendors seeking to institutionalize responsible data practices in an increasingly digitized healthcare environment.